Pre-frontal Cortical Activity During Walking and Turning Is Reliable and Differentiates Across Young, Older Adults and People With Parkinson's Disease - Stuart, Samuel; Belluscio, Valeria; Quinn, Joseph F.; Mancini, Martina (Frontiers in Neurology, 2019)
Introduction Mobility declines with age and further with neurodegenerative disorders, such as Parkinson’s disease (PD). Walking and turning ability, in particular, are vital aspects of mobility that deteriorate with age and are further impaired in PD. Such deficits have been linked with reduction in automatic control of movement and the need for compensatory cognitive cortical control via the pre-frontal cortex (PFC), however the underlying neural mechanisms remain unclear. Establishing and using a robust methodology to examine PFC activity during continuous walking and turning via mobile functional near infra-red spectroscopy (fNIRS) may aid in the understanding of mobility deficits and help with development of appropriate therapeutics. This study aimed to: 1) examine test re-test reliability of PFC activity during continuous turning and walking via fNIRS measurement; and 2) compare PFC activity during continuous turning and walking in young, old and Parkinson’s subjects. Methods Twenty-five young (32.3±7.5 years), nineteen older (65.4±7.0 years) and twenty-four PD (69.3±4.1 years) participants performed continuous walking and 360° turning-in-place tasks, each lasting 2 minutes. Young participants repeated the tasks a second time to allow fNIRS measurement reliability assessment. The primary outcome was PFC activity, assessed via measuring changes in oxygenated hemoglobin (HbO2) concentrations. Results PFC activity during continuous walking and turning was moderately reproducible (Intra-class correlation coefficient = 0.67). The PD group had higher PFC activation than young and older adults during walking and turning, with significant group differences for bilateral PFC activation (p=.025), left PFC activation (p=.012) and the early period (first 40secs) of walking (p=.007), with greater activation required in PD. Interestingly, older adults had similar PFC activation to young adults across conditions, however older adults required greater activation than young adults during continuous turning, specifically the early period of the turning task (Cohens d = 0.86). Conclusions PFC activity can be measured during continuous walking and turning tasks with acceptable reliability, and can differentiate young, older and PD groups. PFC activation was significantly greater in PD compared to young and older adults during walking, particularly when beginning to walk.